KARAKTERISASI BATU KAPUR ALAM BUKIT JIMBARAN BALI - Y. Ulfa; A.A. B. Putra; I N. Simpen (Jurnal Kimia (Journal of Chemistry), 2019)
This research is about the characterization of naturar limestone in the Bukit Jimbaran area of Bali. The aim of this research was to learn chemical composition and micromorphology of Bukit Jimbaran limestone. The research was conducted in sequential steps as described below i.e. the limestone was grinded and sieved in size of 0.25-0.50 mm. Fine limestone, then was heated by using oven at 1000 C for 24 hours and analyzed by FTIR, XRD and SEM. The Spectra of FTIR showed that O-H, C-H, and C-O were dominantly functional groups, which composed CaCO3 and CaO. The results of CaO crystal measurements using Scherrer equation is 51,39 nm. Micromorphology observation by using SEM showed size shaped (vaterite) of Bukit Jimbaran limestone